2019
DOI: 10.1002/pri.1782
|View full text |Cite
|
Sign up to set email alerts
|

Motor performance improvement through virtual reality task is related to fatigue and cognition in people with multiple sclerosis

Abstract: Background and Purpose People with multiple sclerosis (MS) who undergo rehabilitation need to perform new motor skills or relearn old motor skills. It is not clear whether people with MS retain the ability to improve motor performance or learning. Furthermore, factors that influence motor performance in people with MS need to be investigated. This study explored motor performance in people with MS using virtual reality (VR). The effect of fatigue and cognitive function on motor performance improvement in peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The participants of the group 4 reported on low pressure/tension and also low HR was recorded. Most of these ndings are consistent with the recent studies [30] , reporting on effects of cognitive load on motor performance in people with MS. The study pointed out a strong correlation of the results with the Montreal Cognitive Assessment -MoCA [31] .…”
Section: Exergaming Performance and Functional Outcomessupporting
confidence: 92%
“…The participants of the group 4 reported on low pressure/tension and also low HR was recorded. Most of these ndings are consistent with the recent studies [30] , reporting on effects of cognitive load on motor performance in people with MS. The study pointed out a strong correlation of the results with the Montreal Cognitive Assessment -MoCA [31] .…”
Section: Exergaming Performance and Functional Outcomessupporting
confidence: 92%
“…Changes from the baseline visit (V 1 ) to month 6 (V 3 ) and from the baseline visit (V 1 ) to month 1(V 2 ) will be collected as secondary and exploratory variables, respectively. PROs were selected on the basis of previous studies of rehabilitation that reported statistically significant improvements by using VRR in HRQoL ( 22 , 26 , 47 , 48 ), fatigue ( 19 , 49 ), and ADL ( 26 ). The evaluation of depression and anxiety after VRR has received little attention, despite the fact that the prevalence of these disorders has increased ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…VR's potential to use dual-task therapy for multiple sclerosis patients when paired with a treadmill is currently being studied (133). Furthermore, VR games have been used as motor tasks in MS patients to evaluate the effect of cognitive function and fatigue on motor performance improvement (134). Taken together, these studies highlight the potential role of VR in MS rehabilitation.…”
Section: Applications Of Vr For Rehabilitation Indicationsmentioning
confidence: 99%